Multiscale computer modeling in biomechanics and biomedical engineering - Gefen Amit (Studies in Mechanobiology, Tissue Engineering and Biomaterials, 2013)
This book reviews the state-of-the-art in multiscale computer modeling, in terms of both accomplishments and challenges. The information in the book is particularly useful for biomedical engineers, medical physicists and researchers in systems biology, mathematical biology, micro-biomechanics and biomaterials who are interested in how to bridge between traditional biomedical engineering work at the organ and tissue scales, and the newer arenas of cellular and molecular bioengineering.